Energy Harvesting: High‐Performance Piezoelectric, Pyroelectric, and Triboelectric Nanogenerators Based on P(VDF‐TrFE) with Controlled Crystallinity and Dipole Alignment (Adv. Funct. Mater. 22/2017). (June 2017) - Kim, Jihye; Lee, Jeong Hwan; Ryu, Hanjun; Lee, Ju‐Hyuck; Khan, Usman; Kim, Han; Kwak, Sung Soo; Kim, Sang‐Woo
Abstract : In article number1700702, Sang‐Woo Kim and co‐workers report high‐performance piezoelectric, pyroelectric, and triboelectric nanogenerators based on P(VDF‐TrFE) with controlled crystallinity and dipole alignment. A high‐dipole‐moment solvent enhances the end‐to‐end chain length and chain orientation, and leads to higher crystallinity and better dipole alignment of P(VDF‐TrFE).